Dedication of La Maison Davies, second from left: French Consul General Baron de Pampelonne, seated: Dean Myra L. Herrick, second from right: Joan P. Kvaraceus, J1962, and Dr. Seymour O. Simches, chairman of the Department of Romance Languages, 1960 - Unknown (Tufts Archival Research Center, 2005)
8x10